2023
DOI: 10.1111/iju.15162
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the risk stratification newly defined in the Japanese Urological Association guidelines 2019 for non‐muscle invasive bladder cancer: A multi‐institutional collaborative study

Abstract: Objectives: To validate the risk stratification newly defined in the Japanese Urological Association guidelines 2019 for non-muscle invasive bladder cancer and provide a more accurate stratification model for a heterogeneous intermediate-risk group. Methods: A total of 1610 patients, who underwent transurethral resection, diagnosed with non-muscle invasive bladder cancer in nine collaborating hospitals were retrospectively reviewed. They were classified into low-risk, intermediate-risk, high-risk, and highest-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Miyamoto et al. performed a multicenter retrospective analysis in NMIBC patients, and demonstrated that the JUA guidelines 2019 could stratify recurrence‐free survival (RFS), progression‐free survival (PFS), cancer specific survival (CSS) and overall survival (OS) by dividing patients into 4 risk groups 3 . This study emphasizes the usefulness of this risk stratification for decision‐making in clinical practice.…”
mentioning
confidence: 93%
“…Miyamoto et al. performed a multicenter retrospective analysis in NMIBC patients, and demonstrated that the JUA guidelines 2019 could stratify recurrence‐free survival (RFS), progression‐free survival (PFS), cancer specific survival (CSS) and overall survival (OS) by dividing patients into 4 risk groups 3 . This study emphasizes the usefulness of this risk stratification for decision‐making in clinical practice.…”
mentioning
confidence: 93%
“…Given the substantial heterogeneity in NMIBC, the risks of recurrence, progression, and death vary among patients with varying disease risks. Of note, patients with high‐risk NMIBC are associated with a 30%–40% risk of bladder cancer recurrence and 15%–25% of cancer progression during a 5‐year follow‐up from the initial diagnosis 1,2 …”
Section: Introductionmentioning
confidence: 99%
“…Among newly diagnosed patients, most (70–80%) have non‐muscle‐invasive bladder cancer (NMIBC) forms of the disease, which include Ta, T1 and Tis classifications. Despite having a low lifetime risk of death, these NMIBC forms are characterized by high rates of intravesical recurrence and progression to muscle‐invasive bladder cancer 2,3 . The heterogeneous clinical and biological behaviours of NMIBC require tailored treatment recommendations, such as intravesical chemotherapy and intravesical bacillus Calmette–Guerin (BCG) treatment, as well as follow‐up regimens involving hospital visits and invasive cystoscopy examinations.…”
Section: Introductionmentioning
confidence: 99%